(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2004)
In the Ricla area (Zaragoza, Aragonese Branch of the Iberian Range), at the top of the Yátova Formation, grey-reddish wackestone limestones grade into yellow-green siliciclastic limestones of the Aldealpozo Formation. These changes of facies between the two successive formations are associated with syndepositional palaeoreliefs developed during the Late Oxfordian. The uppermost deposits of the Yátova Formation represent an Oxfordian condensed section, from the upper Bifurcatus Zone (Middle Oxfordian) and Hypselum Zone (Upper Oxfordian). These deposits are interpreted as developed in an open marine, moderately deep carbonate platform, showing uniform low-energy conditions with extremely reduced carbonate and terrigenous background sedimentation, and very low sedimentation rates. The low diversity of the benthic fauna, scarce development of sponge bioherms and ammonite populations inhabiting the platform are palaeobiological criteria which corroborate these palaeoenvironmental conditions. Ammonite assemblages are composed of Sub-Mediterranean taxa. Over 900 ammonite specimens have been collected from the upper Bifurcatus and Hypselum zones. Oppeliidae (45,2%) and Perisphinctidae (37,9 %) are dominant. Aspidoceratidae (14,3%) are common. Haploceratidae (2,2%) are scarce. Two phylloceratids and a lytoceratid have been found. Ammonoids are commonly preserved as concretionary calcareous internal moulds of reelaborated elements. Resedimented shells are scarce. The degree of packing of ammonite remains and the stratigraphical persistence display high values. Taphonomic features indicative of sedimentary starving in deep carbonate platform environments are: 1) high concentrations of reelaborated ammonites, 2) taphonic population of type two, 3) phragmocones completely filled with sediment, and 4) homogeneous concretionary internal moulds, bearing no signs of abrasion, bioerosion or dense encrusting by organisms (such as serpulids, bryozoans or oysters). In conclusion, the occurrence of these ammonite associations confirms the development of an advanced deepening phase, within a 3rd order deepening/shallowing cycle, in the Aragonese platform, during the late Bifurcatus to Hypselum zones.